Comparison of the Effectiveness of Pharmacotherapy With and Without Psycho-Educational Intervention on Executive Functions in Hospitalized Bipolar Patients - Loshgani, Vida (Iranian Journal of Neurodevelopmental Disorders, 2024)
Purpose: This study aimed to compare the effectiveness of pharmacotherapy alone versus pharmacotherapy combined with a structured psycho-educational intervention in improving executive functions among hospitalized patients with Bipolar I Disorder.Methods and Materials: A randomized controlled trial was conducted involving 30 patients diagnosed with Bipolar I Disorder who were hospitalized in psychiatric facilities in Tehran. Participants were randomly assigned to two groups: an experimental group (n = 15) that received both pharmacotherapy and a 15-session psycho-educational intervention, and a control group (n = 15) that received pharmacotherapy alone. Executive functions were measured using three standardized tools: the Wisconsin Card Sorting Test (WCST), Stroop Color and Word Test (SCWT), and Trail Making Test (TMT). Assessments were conducted at pre-test, post-test, and a two-month follow-up. Data were analyzed using repeated-measures ANOVA and Bonferroni post-hoc tests via SPSS version 27.Findings: Results indicated statistically significant improvements in executive function scores over time in both groups; however, the experimental group showed significantly greater gains across all three measures. Repeated-measures ANOVA revealed significant time × group interaction effects for WCST (F(2, 56) = 25.23, p < .001, η² = .47), SCWT (F(2, 56) = 21.72, p < .001, η² = .44), and TMT (F(2, 56) = 18.91, p < .001, η² = .41). Bonferroni post-hoc tests confirmed that improvements in the experimental group from pre-test to post-test and follow-up were significantly greater than those observed in the control group.Conclusion: The findings support the superiority of combining psycho-educational interventions with pharmacotherapy in enhancing executive functions in bipolar patients.